Controls on Wintertime Ventilation in Southern Drake Passage - Lilian A. Dove; Giuliana A. Viglione; Andrew F. Thompson; M. Mar Flexas; Taylor R. Cason; Janet Sprintall (Geophysical Research Letters, 2023)
Abstract Drake Passage is a key region for transport between the surface and interior ocean, but a mechanistic understanding of this exchange remains immature. Here, we present wintertime, submesoscale‐resolving hydrographic transects spanning the southern boundary of the Antarctic Circumpolar Current and the Polar Front (PF). Despite the strong surface wind and buoyancy forcing, a freshwater lens suppresses surface‐interior exchange south of the PF; ventilation is instead localized to the PF. Multiple lines of the analysis suggest submesoscale processes contribute to ventilation at the PF, including small‐scale, O(10 km), frontal structure in water mass properties below the mixed layer and modulation of a surface eddy diffusivity at sub‐50 km scales. These results show that ventilation is sensitive to both submesoscale properties near fronts and non‐local processes, for example, sea‐ice melt, that set stratification and mixed layer properties. This highlights the need for adaptive observing strategies to constrain Southern Ocean heat and carbon budgets.